2018
DOI: 10.18203/issn.2454-5929.ijohns20182704
|View full text |Cite
|
Sign up to set email alerts
|

Otomycosis: a clinical and mycological study

Abstract: <p class="abstract"><strong>Background:</strong> The term otomycosis is used to describe fungal infection of ear i.e. external auditory canal, eardrum. This condition appears as a primary infection or develops along with external bacterial infections as a results of antibiotic therapy. This study was designed to determine the clinical symptoms and fungal flora of otomycosis cases.</p><p class="abstract"><strong>Methods:</strong> A total 100 (53% males, 47% females) cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
4
3
0
Order By: Relevance
“…In our study itching in the ear was the commonest symptom in 57.5% of the patients followed by pain (31.8%) in ear and hearing loss (27.2%), similar findings was found in other studies 19 . The fungus growth mixed with the epithelial debris and cerumen forms characteristic mycotic plug which gives rise to the symptom of blocked ear and hearing loss.…”
Section: Resultssupporting
confidence: 92%
“…In our study itching in the ear was the commonest symptom in 57.5% of the patients followed by pain (31.8%) in ear and hearing loss (27.2%), similar findings was found in other studies 19 . The fungus growth mixed with the epithelial debris and cerumen forms characteristic mycotic plug which gives rise to the symptom of blocked ear and hearing loss.…”
Section: Resultssupporting
confidence: 92%
“…This study found that 19.1% of clinical specimens of otomycosis patients in Indonesia demonstrated bacterial co-Table infections, consistent with the documented range of 6-38% in prior reports [9,14] . The higher isolation rates of S. aureus (66.7%) and P. aeruginosa (22.2%) align with the results of previous studies identifying these bacteria as predominant bacterial pathogens in otomycosis [15] .…”
Section: Discussionsupporting
confidence: 91%
“…The temperature and humidity of external auditory canal is usually conducive for growth of Aspegillus sp. This could be one of the reasons for its dominance as etiologic agent for otomycosis [18]. A striking result in this study was coinfection of Candida albicans and Penicillium sp.…”
Section: Discussionmentioning
confidence: 49%
“…This is in agreement with the result obtained from this study. However, Fasunla et al [16], Nazeer et al, [17] and Singh et al [18] reported the dominance of Aspergillus sp. in the ear swab of otomycosis patients.…”
Section: Discussionmentioning
confidence: 99%